Effects of batter - coated methylcellulose on potato substrate during the frying process - Lua, Hwee Ying (2021)
Food hydrocolloids, i.e., hydrolyzed methylcellulose, with thermal gelation properties, are widely used as batter mixtures to coat the fried food prior to the frying process. Properties of hydrocolloids able to satisfy population’s food demand by introducing health-benefits food in conjunction with public health concerns worldwide such as obesity. To study the coating mechanism's advantages, the hydrolyzed Methylcellulose (MC) that, possessed with thermal-reversible properties, was coated onto a potato substrate and investigated along the frying process. Different MC concentration samples between 0.5-2.0 w/v% were subjected to ultrasound treatment (UT) at 20 W to improve the prepared batter mixtures' rheological behaviour and physiochemical properties of fried food. Application of UT to methylcellulose (UTMC) clearly showed a phase transition from fluid- to gel-like between 20 °C and 65 °C with the increase in the oscillation frequency and temperature ramp test. UTMC method also showed lower sol-gel transition occurrence than non-UTMC at 25 °C and 30 °C respectively, within the linear viscoelastic region. When the MC concentrations were varied, the most effective concentration for coating purposes was noticed to occur at 1.0 (w/v%) UTMC, whereby the water retention and oil uptake was reduced to 39.3% and 56.9 %, respectively, as compared to 1.0 w/v% non-UTMC formulation. The batter-coated fried food also showed a significant decrease in the acrylamide concentration. The amount of acrylamide in 1.0 w/v% MC was reduced from 156.40±7.44 ng/g to 64.8 ±5.05 ng/g in 1.0 w/v% UTMC. In conclusion, this work's findings provide further insights into the influence of hydrocolloids as an effective layer to improve the quality of the fried products.